Memories of Faraway Visitors to Southeast Asia: the ‘Portuguese fort’ in Amurang - Schouten, Maria Johanna (ILUMINURAS, 2019)
ABSTRACT: This article examines today’s perception among Indonesians of the Portuguese presence in Eastern Indonesia during the sixteenth and seventeenth centuries. Despite evidence of the often violent pursuit of supremacy and material benefit by European navigators, the local population has different understandings of the past. An assessment of these from an anthropological perspective is guided by twin concepts such as emics and etics, and memory and history. Our case study combines documentary research and fieldwork, focusing on a colonial fort in the town of Amurang, on the island of Sulawesi. The present-day accounts of the local population and of some official organizations attribute a Portuguese origin to this fort, and narratives about the Portuguese abound in folk memory, often contradicting the findings of scientific research. Most significant is the positive image of the Portuguese prevalent among the population. The article includes historical data on the Portuguese and Spanish presence in Indonesia and ethnographic data of Amurang, as well as architectural and archaeological details of the fort. Keywords: Forts Folk memories Postcolonialism Portuguese Indonesia Memórias de visitantes longínquos ao Sudeste Asiático: a ‘fortaleza portuguesa’ em Amurang RESUMO: Este artigo examina a perceção existente na atualidade entre os indonésios relativamente à presença portuguesa no arquipélago entre os séculos XVI e XVII. Apesar de as evidências demonstrarem que a busca por supremacia e benefícios materiais por parte de navegadores europeus foi realizada com recurso à violência, a população local apresenta versões diferentes deste passado. Numa análise destas versões, seguindo uma abordagem antropológica, é útil a aplicação de binómios como emics e etics, e memória e história. Para o presente estudo foi efetuada investigação de terreno e documental sobre um forte colonial da cidade de Amurang, na ilha de Sulawesi. Nas numerosas narrativas populares e no discurso oficial sobre os portugueses, estes foram os construtores deste forte, contradizendo conclusões de investigação científica. Sobressai a prevalência junto da população de uma imagem positiva dos portugueses. O artigo inclui informação histórica relativa à presença portuguesa e espanhola na Indonésia, dados etnográficos de Amurang, assim como detalhes arquitetónicos e arqueológicos do forte. Palavras-chave: Fortalezas; Memórias populares; Pós-colonialismo; Portugueses; Indonésia